Revolutionizing Consumer-Brand Relationships In Telecom Sector And Beyond: Exploration & Study Of Generative AI In Improving Customer Service Experience - Jayaraman, Karthik (Digital Repository of Theses, 2025)
This study investigates the use of generative artificial intelligence (GAI) in enhancing consumer-brand interactions within the telecom industry. The purpose of the study is to find a solution for the ever-escalating request for customer service that is highly GAI responsive, effective, and speedy. The research is conducted using a mixed-methods approach; quality-focused interviews with industry professionals were computed with quantitative service performance metrics for leading telecom providers. This research has been designed to shed light on real-world challenges facing GAI in the telecom sector, and how they can be addressed in future work, bringing value and overcoming the existing barriers. This research reinforces the fact that emerging technologies should be embraced as need arises for greater prospects in serving the customers and sustaining competition in the digital world.